2004
DOI: 10.1021/jm031132g
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimalarial Activity of a Series of Cationic 2,2‘-Bipyridyl- and 1,10-Phenanthrolineplatinum(II) Benzoylthiourea Complexes

Abstract: We have synthesized a series of novel 2,2'-bipyridyl and 1,10-phenanthroline benzoylthiourea complexes of platinum(II) with various substituents on the bipyridyl and phenanthroline ligands. All of these square-planar mixed-ligand cationic complexes were found to form moderately strong complexes with ferriprotoporphyrin IX in 40% aqueous DMSO (log K ranging from 4.81 to 6.24). The complexes also all inhibit beta-hematin (synthetic hemozoin or malaria pigment) formation in acetate solution. Four of the compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 45 publications
(173 reference statements)
2
72
0
Order By: Relevance
“…For example, acylthiourea derivatives and their Co(III) complexes have shown antibacterial [13] and antifungal [14] activities. Ni(II) complexes, containing benzoylthiourea ligands, have shown cytotoxicity against T47D cell [15] and according to the investigations water soluble platinum(II) benzoylthiourea complexes have shown considerable antimalarial activity [23,24]. Very recently, there have been many studies on noncovalent interactions acting on the crystal structure and packing of sulfur-containing compounds [25].…”
Section: N-(alkyl/aryl)-n'-acylthiourea and N-di(alkyl/aryl)-n´-mentioning
confidence: 99%
“…For example, acylthiourea derivatives and their Co(III) complexes have shown antibacterial [13] and antifungal [14] activities. Ni(II) complexes, containing benzoylthiourea ligands, have shown cytotoxicity against T47D cell [15] and according to the investigations water soluble platinum(II) benzoylthiourea complexes have shown considerable antimalarial activity [23,24]. Very recently, there have been many studies on noncovalent interactions acting on the crystal structure and packing of sulfur-containing compounds [25].…”
Section: N-(alkyl/aryl)-n'-acylthiourea and N-di(alkyl/aryl)-n´-mentioning
confidence: 99%
“…[1][2][3][4][5] Our interest in the chemistry of planar, cationic mixed-ligand Pt II complexes of the general type [Pt II (diimine)(L n -S,O)] + (where diimine is 2,2-bipyridine or 1,10-phenanthroline and HL n -S,O are various chelating N-acyl-N,Ndialkylthioureas) arises from their interesting biological activity ranging from potential anti-malarial activity 6 to DNAintercalation and demonstrable in vivo activity toward bacterial E. coli AB1886 (uvr A) cultures. 7 Preliminary work also shows that such complexes undergo some interesting DNA-templated 'biomineralization'.…”
Section: Introductionmentioning
confidence: 99%
“…7 Preliminary work also shows that such complexes undergo some interesting DNA-templated 'biomineralization'. 8 The in vitro anti-malarial activity 6 (1,10-phenanthroline Table 1. Doty and Myers attributed similar trends in ΔΔ r S 0 for dimerization of protein moieties to the dehydration of charged groups upon aggregation, while Kauzmann and Scheraga suggested that this trend may be due to non-covalent hydrophobic bonding of non-polar groups increasing the degree of freedom of the water molecules close to hydrophobic groups.…”
Section: Introductionmentioning
confidence: 99%
“…As our interests lie also in the area of antiparasitic drugs [42,43] and since a few Pt(II) [44] and Pd(II) based complexes [45] with antimalarial activity (in the micromolar range) have been reported, we also tested the potential of the free ligands (1a-1c) and the complexes 2a-5c against the chloroquine-susceptible strain (3D7) and the chloroquine-resistant strain (W2) of Plasmodium falciparum.…”
mentioning
confidence: 99%